2017
DOI: 10.1097/rti.0000000000000276
|View full text |Cite
|
Sign up to set email alerts
|

Crus Atrophy

Abstract: Atrophy of the crus assessed by CT is a good discriminator of paralyzed versus nonparalyzed hemidiaphragm in patients with suspected diaphragmatic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…On coronal images, the right and left pillars were measured along the middle of the anterior part of L1 (Fig. 1B), according to the results found in the study of Sukkasem et al [10]. On coronal images, the difference in height between the two domes was measured in the anterior part of L1 (Fig.…”
Section: Ct Scan Evaluationmentioning
confidence: 60%
See 1 more Smart Citation
“…On coronal images, the right and left pillars were measured along the middle of the anterior part of L1 (Fig. 1B), according to the results found in the study of Sukkasem et al [10]. On coronal images, the difference in height between the two domes was measured in the anterior part of L1 (Fig.…”
Section: Ct Scan Evaluationmentioning
confidence: 60%
“…Compared with diaphragmatic ultrasonography, CT is capable of fully describing the anatomy of the diaphragm [9], is more available, not operator-dependent, and reproducible. In unilateral diaphragmatic paralysis, it has been shown that the pillars of the diaphragm become thinner and can be measured by CT [10]. In addition, measurement of pillar thickness at the level of the celiac artery and L1 has shown good intra-and inter-observer reproducibility [11].…”
Section: Introductionmentioning
confidence: 99%
“…A crus thickness <2.5 mm has a high sensitivity and specificity for diaphragm dysfunction. 3 Abnormal thickness was considered when thickness was <2.5 mm at the celiac artery level (minimal thickness on the axial cuts) and/or <2.5 mm at the L1 vertebral level (at the anterior part on the coronal cuts).…”
Section: Methodsmentioning
confidence: 99%
“…Diaphragm thickness was measured using computerized tomography scan-based measurement of "crus" thickness at the levels of the celiac and superior mesenteric arteries and the L1 vertebral body as previously described. 3 Absolute measurements were included. The diaphragm thickness is preferentially measured at the crus than the dome of the diaphragm.…”
Section: Diaphragm Thicknessmentioning
confidence: 99%
“…Asymmetric thinning of the diaphragmatic crus (<2.5 mm thickness on axial computed tomography [CT] at the level of L1) is a manifestation of denervation atrophy from local neuromuscular injury (phrenic nerve injury) and often accompanies hemidiaphragmatic paralysis (Fig. 3) while systemic neuromuscular disorders usually result in bilateral atrophy 6…”
Section: Diaphragmatic Dysfunctionmentioning
confidence: 99%